The Urgency Of Implementing 5g In Increasing Village Community Resources - Hartati, Hartati; Ramayanti, Herni; Wandi, Didi; Safitri, Elvina; Wulandari, Wulandari; Masduki, Damayanti (Journal Of Human And Education (JAHE), 2024)
After providing service for approximately 1 month, researchers discovered the potential for developing human resources and the economic welfare of village communities by developing internet quality from 2G, 3G and 4G to 5G. Therefore, this article aims to analyze The Urgency Of Implementing 5g In Increasing Village Community Resources. The results of this article show 1. The 5G network has advantages compared to the 2G, 3G and 4G networks that have been implemented in these villages, namely: a) Has a data transfer speed of 1 millisecond, b) Can be connected to equipment such as cars, household appliances and telephones, c) Has a more comparable speed. 2. Service members found complaints about slow internet for digital business actors in these villages when conducting initial observations. The servants discuss with village officials about implementing a 5G network and village officials agree if there are investors and funding from the government or other parties. 3. The existence of a 5G network in these villages has 3 main urgencies, namely: a) Increase digital business productivity. b) Improving Human Resources in rural communities. c) Creating new business models and expanding digital business.